Konstruksi Model Kualitas Laporan Keuangan Di Indonesia - Oyong Lisa; Abdul Halim (Universitas Muhammadiyah Malang, 2023)
The purpose of this study is to construct a financial report quality model that includes professional supervision as a moderator of the relationship between audit quality and competence and independence, and audit quality as a mediation effect of competence and independence on the quality of financial reports. Perceptions of Public Accountants (AP) on competence, independence, audit quality, professional supervision, and quality of financial reports are the subject matter of primary data collected by purposive sampling from 678 KAPs in Indonesia. Partial Least Square is used to analyze. The t test was applied to test the hypothesis. The research findings show that the financial report quality model is created by first strengthening the relationship between competence and independence with audit quality through professional supervision. The relationship between professional supervision and audit quality is getting stronger the tighter it is. Second, audit quality as a mediator has the potential to strengthen the impact of competence and independence on the quality of financial reports. The impact on the quality of financial reports increases along with audit quality.